Effects of chronic salicylate on GABAergic activity in rat inferior colliculus - Bauer, C.A; Brozoski, T.J; Holder, T.M; Caspary, D.M (Hearing research, 2000)
It is well accepted that salicylate ototoxicity results in reversible tinnitus in humans. Salicylate-induced tinnitus may be an example of plasticity of the central auditory system and could potentially serve as a model to further understand mechanisms of tinnitus generation. This study examined levels of glutamic acid decarboxylase (GAD) and the binding characteristics of the GABA A receptor in auditory brainstem structures of Long–Evans rats chronically treated with salicylate. Western blotting revealed a significant 63% ( P<0.008) elevation of GAD levels in the inferior colliculus (IC) of salicylate-treated subjects. This occurred in subjects demonstrating behavioral evidence of tinnitus. Muscimol saturation analysis was indicative of a salicylate-related increase in receptor affinity. Linear regression of [ 3H]muscimol saturation analysis data revealed a significant ( P<0.05) reduction in K d values in whole IC (−48%), as well as in the central nucleus of IC (CIC, −58%) and combined external and dorsal cortex of IC (E/DCIC, −46%). The number of GABA A binding sites ( B max) were also significantly ( P<0.05) decreased. These changes were observed only in central auditory structures. This suggests that GAD expression and GABA A receptor binding characteristics may be altered with chronic exposure to sodium salicylate and these changes may represent aberrant plasticity clinically experienced as tinnitus.